2011
DOI: 10.1371/journal.pone.0028937
|View full text |Cite
|
Sign up to set email alerts
|

Which Is the Most Suitable Classification for Colorectal Cancer, Log Odds, the Number or the Ratio of Positive Lymph Nodes?

Abstract: ObjectiveThe aim of the current study was to investigate which is the most suitable classification for colorectal cancer, log odds of positive lymph nodes (LODDS) classification or the classifications based on the number of positive lymph nodes (pN) and positive lymph node ratio(LNR) in a Chinese single institutional population.DesignClinicopathologic and prognostic data of 1297 patients with colorectal cancer were retrospectively studied. The log-rank statistics, Cox's proportional hazards model, the Nagelker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…The lymph node ratio (LNR), defined as the number of involved nodes divided by the number of lymph nodes examined, was found to improve prognostic information in breast cancer, gastric cancer, colorectal cancer, melanoma and others. [6], [7], [8], [9], [10], [11], [12] Approximately 60% to 80% of patients with hypopharyngeal cancer have locally advanced disease with spread to regional nodes at diagnosis. [13] However, there have been no previous studies on the impact of the LNR on predicting the prognosis of hypopharyngeal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The lymph node ratio (LNR), defined as the number of involved nodes divided by the number of lymph nodes examined, was found to improve prognostic information in breast cancer, gastric cancer, colorectal cancer, melanoma and others. [6], [7], [8], [9], [10], [11], [12] Approximately 60% to 80% of patients with hypopharyngeal cancer have locally advanced disease with spread to regional nodes at diagnosis. [13] However, there have been no previous studies on the impact of the LNR on predicting the prognosis of hypopharyngeal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the LODDS classification was found to be superior to the pN and LNR classifications in Chinese patients with CRC undergoing R0 curative resection for the first time. Song et al (32) revealed that, for Chinese patients with CRC, the LNR classification was more suitable compared with the pN and LODDS classifications for prognostic assessment. Several reasons may have contributed to these different results: i) The cut-off points acquired from different statistical methods for subclassification were different; ii) the proportion of colon and rectal cancer patients was different; and iii) the time interval between the date of the last patient undergoing curative resection to the follow-up deadline (October, 2015) was different.…”
Section: Lnr N (%) Lodds N (%) ------------------------------------mentioning
confidence: 99%
“…Therefore, increasing attention has been paid to lymph node status, which can be evaluated by the number of resected lymph nodes (RLNs), lymph node ratio (LNR), and the log odds of positive lymph nodes (LODDS) . Compared to a single parameter, LNR exhibits its advantage in breast, pancreatic, colon, and ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a single parameter, LNR exhibits its advantage in breast, pancreatic, colon, and ovarian cancers. Another parameter, LODDS, showed superiority in predicting outcomes in breast, pancreatic, colorectal, and ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%